A 3D Printed Wearable Bioelectronic Patch for Multi‐Sensing and In Situ Sweat Electrolyte Monitoring. Issue 4 (14th January 2021) - Kim, Taeil; Yi, Qian; Hoang, Emily; Esfandyarpour, Rahim
Abstract: Wearable biosensors′ ability to measure continuous health parameters gives promise to healthcare with great potentials to advance precision medicine. The stability and balance within the human body are critical for organ systems′ normal functions. The imbalance of electrolytes may lead to several diseases such as hypertension, heart failure, and kidney diseases. Sweat electrolytes analysis, that is, the analysis of one of the noninvasively accessible biofluids, can provide important information about physiologically relevant quantities, and a combination of them can be employed for comprehensive studies. However, wearable biosensors′ large‐scale utilization for extensive population monitoring requires rapid, reliable, low‐cost, and high‐throughput integration of such platforms. Here, 3D‐printing technology is adapted to develop a novel, multiplex, low‐cost, and mechanically flexible all‐inclusive integrated wearable (AIIW) patch, which contains 3D‐printed flexible sensors along with flexible wearable‐microfluidic sample handling (WMFSH) units, integrated in a few hours. The AIIW patch is fully characterized, and its utility for noninvasive and continuous health monitoring is successfully demonstrated by simultaneous ex situ and in situ measuring of multiple electrolyte levels in sweat. This work is envisioned as another step toward enabling personalized health monitoring practices by implementing 3D‐printing technology in the easy and low‐cost development of customized integrated, flexible wearable biosensing platforms to monitor an individual's health parameters. Abstract : A 3D‐printed bioelectronic wearable patch for multi‐sensing and in situ sweat electrolyte monitoring, along with a flexible wearable‐microfluidic unit, is developed, and its utility for noninvasive health monitoring is demonstrated. This work is envisioned as another step toward enabling personalized health monitoring by implementing 3D‐printing technology in the easy and low‐cost development of customized integrated wearable biosensing platforms to monitor individuals' health parameters.